Characterisation of Robust Combustion Catalyst from Aluminium Foil Waste. Issue 5 (6th February 2018) - Osman, Ahmed I.; Abu‐Dahrieh, Jehad K.; McLaren, Mathew; Laffir, Fathima; Rooney, David W.
Abstract: Herein a robust and active combustion catalyst was prepared with three‐quarter (75 wt.%) of its composition derived from the aluminium foil waste and designated as 5Pd‐ACFL550. The prepared catalyst was characterised using X‐ray diffraction (XRD), Temperature‐programmed reduction (TPR), Bright‐field transmission electron microscopy (BF‐TEM), High angle annular dark field (HAADF), Fourier transform infrared‐pyridine (FTIR‐Pyridine) and X‐ray Photoelectron Spectroscopy (XPS) techniques and compared to the commercial equivalent (5Pd‐AC550). The catalyst 5Pd‐ACFL550 showed higher catalytic activity than that of 5Pd‐AC550 in the total methane oxidation reaction with T50% at 303 °C at Gas hourly space velocity (GHSV) of 100, 000 mL g −1 h −1 . Our approach opens doors for the preparation of robust cheap combustion catalyst from aluminium foil waste and demonstrates its application in the catalytic converters of natural gas vehicles (NGV‐vehicles) and other combustion applications. As a result, this can be opened up to a wider variety of application markets, including residential and automotive applications. Abstract : Herein a robust and active combustion catalyst was prepared with three‐quarter (75 wt.%) of its composition derived from the aluminium foil waste. Microscopic techniques revealed that catalyst structure is dominated by alumina, with Ti found around the edges. These results open doors for the preparation of highly active and well‐structured nano‐mesoporous alumina catalyst/support from aluminium foil waste and its application in acid catalysed reactions and especially in combustion reactions.